Comparative analysis of species composition and recourses of drug plants at Kazakhstan Altay (Experimental biology, 2015)
The article presents analysis of species composition and recourses of drug plants at Western Altay, Naryn and Kalbinskiy ridges with difference in species diversity and huge resource potential. The article contains the analysis of the relation between families and medicinal species of the area under study, which allowed to reveal the large and medium-sized families. There is conducted an environmental analysis of the drug plants flora and nine environmental groups are identified with regard to moisture. It was determined that xerophytes and mezoxerophytes are dominants among the drug plants. The obtained data revealed that according to number and types of drug plants Holzun, Listvyaga, Koksu,Ivanovo, Ulbinsk, and Naryn ridges are of great practical interest; Western Altai ranges, as well as the central and eastern part of Naryn range differ by the greatest diversity of drug plants species.
Keywords: flora; resources; drug plants; ecology; xerophytes